Eros and politics - Rønning, Helge (Nordlit, 2015)
There are many parallels between Henrik Ibsen’s Rosmersholm (1886) and Bjørnstjerne Bjørnson’s Paul Lange og Tora Parsberg (1898). Both dramas have as their protagonist a weak and noble man, who is offered love and an erotic relationship by a strong woman, and who is not able to reciprocate. At the same time they are plays about how politics demand the ability to act and take a stand in a world where men are supposed to engage politically at the same time as women are supposed to stand in the background. In both dramas the political and the erotic are interwoven in a manner that drives the men into despair because they can neither satisfy the demands of love in the intimate arena nor the demands for power in the public arena of politics. There are also other parallels between the plays, in relation to the role of the figures, that demand of the protagonists that they take a stand, and drop them and betray them when they do not. Both dramas also end in a final suicide. Though here the two plays differ in that in Ibsen’s play the drama ends in the double suicide of the man and the woman, while in Bjørnson’s it is only the man who sacrifices himself. This implies that the question of strength, power and the erotic are more consistently played out in Ibsen’s drama.